DEVELOPMENT STRATEGY GAP IN SOCIAL POLICY - SOCIAL PROBLEM INTERACTION: APPRAISAL OF NATIONAL POVERTY ERADICATION PROGRAMME IN RURAL COMMUNITIES OF AKWA IBOM STATE, NIGERIA. - Festus, Nkpoyen; Ugo Chuks, Okolie,; Onyema, Okwu A.; , Esther P, Archibong; , Brown E, Isokon; Chimaobi, Okorie,; Fidelis Ngaji, Akwaji,; Glory, Bassey (International Journal of Psychosocial Rehabilitation, 2024)
The study investigated development strategy gap in social policy and social probleminteraction by examining the impact of the social welfare policy of NAPEP on ruralcommunities in AkwaIbom State of Nigeria. Specific objectives were to demonstrate the  extent to which existing implementation gap foisted by non-participation of benefittingcommunities in poverty eradication programme, diversion of programme funds throughcorruption and non-commitment to policy execution impact on poverty reduction in ruralcommunities. Relevant and related literature was reviewed. The human development(capability approach) was adopted as the theoretical framework. The Expost facto researchdesign was adopted. Two local government areas (Oron and Udung Uko) constituted thestudy areas. Multistage sampling procedure was utilized to obtain the data using a 26-itemresearch instrument from 400 respondents determined through the use of Taro Yamenesample size determination formula. Data were analysed using Chi-square(X2) statisticaltechnique. Thestudy revealed that a significant association exists between non-participationof beneficiary communities in poverty eradication project design/implementation at locallevel and poverty reduction in rural communities; a significant relationship exists betweencorrupt practices and poverty reduction in rural communities, poor policy implementationstrategy has a significant association with poverty reduction in rural communities. Analysesof data revealed that the calculated (x2) values of 42.46, 192.82 and 20.03 respectively werehigher than the critical value of 7.81 Although NAPEP, the government interventionstrategy has the potential to reduce poverty, but it has not been able to lift rural dwellers outof extreme poverty because of development gaps induced by non-inclusion of beneficiariesin program decisions, corrupt practices and poor policy implementation. Rural dwellershave not experienced the impact of NAPEP.